2012
DOI: 10.4102/sajs.v108i5/6.880
|View full text |Cite
|
Sign up to set email alerts
|

‘God is my forest’ – Xhosa cultural values provide untapped opportunities for conservation

Abstract: In South Africa conservation is still largely framed in terms of Western scientific values, with a focus on material benefits to local communities, whilst little is known about the intangible values local people attach to nature and biodiversity. We explored the cultural, spiritual and emotional relationships with nature expressed by Xhosa people, within the Maputaland-Pondoland-Albany Hotspot, as well as the activities that mediate this relationship. A descriptive research approach was applied to document the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 23 publications
2
74
0
Order By: Relevance
“…Previous research has noted that more traditional values are often associated with anthropocentric concerns (Schultz & Zelezny, 1999) Westernisation (Jones, 2014). This interpretation is supported by previous research that revealed a strong sense of connectedness with nature amongst rural South Africans, and that rural African people valued and understood biodiversity differently to Western people (Cocks et al, 2012). This interpretation of a duality of worldviews is reinforced by research that shows that, in Southern Africa, traditional (African) as well as scientific (Western) notions of natural phenomena exist concurrently (Breidlid, 2009).…”
Section: African Visitorssupporting
confidence: 65%
See 3 more Smart Citations
“…Previous research has noted that more traditional values are often associated with anthropocentric concerns (Schultz & Zelezny, 1999) Westernisation (Jones, 2014). This interpretation is supported by previous research that revealed a strong sense of connectedness with nature amongst rural South Africans, and that rural African people valued and understood biodiversity differently to Western people (Cocks et al, 2012). This interpretation of a duality of worldviews is reinforced by research that shows that, in Southern Africa, traditional (African) as well as scientific (Western) notions of natural phenomena exist concurrently (Breidlid, 2009).…”
Section: African Visitorssupporting
confidence: 65%
“…The third factor was labelled Nature Distance, as it represented visitors' personal distance from nature. It is suggested that the construct Nature Distance is particularly relevant to the South African situation, and is better suited to a context in which urbanisation is seen as progress and nature experiences are thought of as less progressive (Cocks et al, 2012). The construct may also reflect the challenges experienced by many respondents in handling negatively worded items.…”
Section: Connectedness To Nature (Nature Relatedness)mentioning
confidence: 99%
See 2 more Smart Citations
“…Consider now, how women elsewhere in Eastern Cape variously feel freedom and bonds with others and with their ancestors as they walk through the forest together gathering fuelwood, proud of the size and neatness of their woodpiles. Without access to forests, women miss these experiences and feel less of a mother and hard working adult woman [Cocks et al 2012]. This article is not about forest depletion, carbon politics or fuelwood; but it is about practices in which walking, to access and use resources, including electricity, links together bodies, sociality, physical environments, and felt experiences.…”
Section: Introductionmentioning
confidence: 99%